Self‐Powered Non‐Contact Motion Vector Sensor for Multifunctional Human–Machine Interface. Issue 8 (22nd June 2022) - Cao, Jie; Fu, Xianpeng; Zhu, Hao; Qu, Zhaoqi; Qi, Youchao; Zhang, Zhi; Zhang, Zhongqiang; Cheng, Guanggui; Zhang, Chi; Ding, Jianning
Abstract: Sensors as the significant units of the Internet of Things play an important role in the field of information interaction. Non‐contact sensors have the advantages of flexible manipulation and a longer lifespan but it is constrained in motion detection due to their relative single detection function. Herein, a self‐powered non‐contact motion vector sensor (NMVS) for the multifunctional human–machine interface is reported. Based on the electrostatic induction effect, the motion vector is measured according to the output electrical signals from the non‐contact triboelectric nanogenerator (NC‐TENG). By simulation analysis and experimental validation, the output characteristics of NC‐TENG dependence on structural and motion parameters are investigated in detail. On this basis, the resolution of NMVS is improved and exhibits for non‐contact micro‐vibration monitoring, rehabilitation gait detection, contactless smart lock, and the non‐contact limit alarm. This work not only proposes an ingenious strategy for non‐contact motion vector detection but also demonstrates the promising prospects of a multifunctional human–machine interface in intelligent electronics, health rehabilitation, and industrial inspection. Abstract : Herein, a self‐powered non‐contact motion vector sensor (NMVS) for multifunctional human–machine interface is reported. Based on the output characteristics of non‐contact triboelectric nanogenerator, an ingenious strategy is developed to improve the resolution of NMVS in motion detection. Furthermore, the capability of NMVS in non‐contact micro‐vibration monitoring, rehabilitation gait detection, contactless smart lock, and limit alarm is demonstrated.